2022
DOI: 10.3390/antiox11050946
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor NRF2 Participates in Cell Cycle Progression at the Level of G1/S and Mitotic Checkpoints

Abstract: Transcription factor NRF2 is a master regulator of the multiple cytoprotective responses that confer growth advantages on a cell. However, its participation in the mechanisms that govern the cell division cycle has not been explored in detail. In this study, we used several standard methods of synchronization of proliferating cells together with flow cytometry and monitored the participation of NRF2 along the cell cycle by the knockdown of its gene expression. We found that the NRF2 levels were highest at S ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…They found that the knockout of NRF2 in A549 and NCI-H292 cells caused cell cycle arrest in the G1 phase. Furthermore, other in vitro experiments showed that a lack of NRF2 prevented cell cycle progression and slowed cell proliferation [80,81]. Moreover, there are few reports of the relationship between NQO1 and cyclin E-CDK2.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the knockout of NRF2 in A549 and NCI-H292 cells caused cell cycle arrest in the G1 phase. Furthermore, other in vitro experiments showed that a lack of NRF2 prevented cell cycle progression and slowed cell proliferation [80,81]. Moreover, there are few reports of the relationship between NQO1 and cyclin E-CDK2.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that PTEN-induced kinase 1 (PINK1) has a critical function in maintaining mitochondrial integrity and protecting cells from oxidative stress. Research shows that NRF2 positively influences PINK1 production and that the NRF2–PINK1 signaling pathway is critical for cell survival [ 86 ].…”
Section: Role Of Nrf2 In Senescencementioning
confidence: 99%
“…Recently, Lastra et al showed that NRF2 levels oscillate during cell-cycle progression, reaching a peak in G1/S and being minimal in G2/M [ 65 ] ( Figure 3 ). The decrease in NRF2 levels leads to an increase of cells in G1 as they are not ready to enter the S-phase with subsequent cycle arrest at the G1/S restriction point.…”
Section: Nrf2 Beyond Its Antioxidant Rolementioning
confidence: 99%
“…Thus, NRF2 is required for the expression of positive regulators (cyclin-dependent kinase (CDK)-2, and the transcription factor Dp-1, TFDP1) and the repression of the negative regulators cyclin dependent kinase inhibitor 1A (CDKN1A), and cyclin dependent kinase inhibitor 1B (CDKN1B) of the G1-S transition. In addition, it is also involved in the optimal expression of genes involved in DNA damage detection (cyclin-G1, CCNG1) and repair (DNA repair protein RAD51 homolog 1, RAD51) [ 65 ] ( Figure 3 ). On the other hand, as has been demonstrated in NRF2-deficient mice, a reduction in the levels of this transcription factor releases KEAP1 from its binding and allows it to bind to other proteins such as p21 at the G1/S transition [ 66 ].…”
Section: Nrf2 Beyond Its Antioxidant Rolementioning
confidence: 99%